2015
DOI: 10.1037/hea0000295
|View full text |Cite
|
Sign up to set email alerts
|

Pilot RCT of bidirectional text messaging for ART adherence among nonurban substance users with HIV.

Abstract: Objective This pilot study tested the preliminary efficacy of a theory-based bidirectional text messaging intervention (TEXT) on antiretroviral (ART) adherence, missed care visits, and substance use among people with HIV. Methods Participants with recent substance use and ART nonadherence from 2 nonurban HIV clinics were randomized to TEXT or to usual care (UC). The TEXT intervention included daily queries of ART adherence, mood, and substance use. The system sent contingent intervention messages created by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 48 publications
(64 reference statements)
2
101
0
Order By: Relevance
“…Half (k = 7) of these efficacious, theory-based eHealth interventions were US-based [32] [33] [24, 30, 31, 34, 35]. Most (k = 11) of these efficacious, theory-based interventions implemented eHealth using electronic devices that were more technologically advanced (e.g., multimedia messaging) instead of or in conjunction with SMS texting.…”
Section: Resultsmentioning
confidence: 99%
“…Half (k = 7) of these efficacious, theory-based eHealth interventions were US-based [32] [33] [24, 30, 31, 34, 35]. Most (k = 11) of these efficacious, theory-based interventions implemented eHealth using electronic devices that were more technologically advanced (e.g., multimedia messaging) instead of or in conjunction with SMS texting.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the papers on simple interventions reported on changes in use of other services. Gonzales [48] reported significantly higher attendance at self help meetings and recovery oriented activities among those in the experiment condition compared to controls, and Ingersoll [50] reported that the adherence to antiretroviral treatment increased by 19 percentage points in the experimental condition compared to a 9 percentage point increase in the treatment as usual condition. Bischof [80] reported a drop in face to face counseling time of 50% in the experimental condition, while Lucht [51] reported that the participants in the experimental condition spent significantly more days than the controls in psychiatric hospital.…”
Section: Intervention Effects On Other Outcomesmentioning
confidence: 99%
“…The rest of the interventions were less intense and had a longer duration. In these, participants typically received and sent two messages each day for three months [35] or 10 months [50], one message each day for two to four months [39,42,45,55,56], or one each week for six months [49]. There is not much information in the papers documenting whether the participants actually read the messages they received.…”
Section: Intensity and Duration Of The Interventionsmentioning
confidence: 99%
See 2 more Smart Citations